MULTIDISCIPLINARY APPROACH TO IMPLANTATION OF RESYNCHRONIZING DEVICES - An. M. Osadchiy; A. V. Kamenev; M. V. Agarkov; N. E. Pavlova; S. V. Vlasenko; S. V. Lebedeva; S. G. Shcherbak; D. S. Lebedev (Российский кардиологический журнал)
.